2006
DOI: 10.1530/eje.1.02136
|View full text |Cite
|
Sign up to set email alerts
|

Is there a need to redefine the upper normal limit of TSH?

Abstract: Mild forms of hypothyroidism -subclinical hypothyroidism -have recently been discussed as being a risk factor for the development of overt thyroid dysfunction and for a number of clinical disorders. The diagnosis critically depends on the definition of the upper normal limit of serum TSH as, by definition, free thyroxine serum concentrations are normal. Cut-off levels of 4-5 mU TSH/l have been conventionally used to diagnose an elevated TSH serum concentration. Recent data from large population studies have su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
2
17

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(131 citation statements)
references
References 46 publications
4
108
2
17
Order By: Relevance
“…Free thyroxine (F-T4), free triiodothyronine (F-T3), and thyroid stimulating hormone (TSH) and insulin were measured on cobas e 601 module (Electrochemiluminescence Technology, Roche Diagnostics), while the remaining analytes on cobas c 501 clinical chemistry module (Photometric Technology), according to the instructions of the manufacturer. TSH was considered normal if it was between 0.4 and 4.0 mIU/L [ 28 ]. The reference intervals for FT3 and FT4 were 2.70-5.20 pg/mL and 0.80-1.90 ng/dL, respectively These biochemical parameters are routine tests for the patients that are followed-up and treated at the YorkTest Turkey Laboratory.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Free thyroxine (F-T4), free triiodothyronine (F-T3), and thyroid stimulating hormone (TSH) and insulin were measured on cobas e 601 module (Electrochemiluminescence Technology, Roche Diagnostics), while the remaining analytes on cobas c 501 clinical chemistry module (Photometric Technology), according to the instructions of the manufacturer. TSH was considered normal if it was between 0.4 and 4.0 mIU/L [ 28 ]. The reference intervals for FT3 and FT4 were 2.70-5.20 pg/mL and 0.80-1.90 ng/dL, respectively These biochemical parameters are routine tests for the patients that are followed-up and treated at the YorkTest Turkey Laboratory.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…This suggestion raised a storm of controversy (29)(30)(31). Despite the fact that examination of individuals was not based on NACB guidelines, which was not published when data were collected for our study, our interval limits can be assumed to be correct for middle-aged French adults.…”
Section: Discussionmentioning
confidence: 96%
“…Another limitation of our study is the less well-standardized time of blood specimen collection. It has been previously reported that serum TSH levels might alter by daytime (35). Therefore, we performed analyses stratified by the time of blood sampling, which did not change the results materially.…”
Section: Discussionmentioning
confidence: 99%